Implementation of Multicultural Islamic Education in Higher Education in an Effort to Reconstruct Students' Inclusive Character - Pratiwi Tri Aminah; Fery Diantoro; Nurfida Mardatillah; Shofiatuz Zahroh (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
This research is motivated by the phenomenon in higher education where many students still have intolerant attitudes and lack inclusive attitudes. This study was conducted with the aim of describing and analyzing the role of multicultural Islamic education in building the inclusive character of students in higher education. The method used is a descriptive qualitative method with a literature study approach. Data in this study were obtained by collecting, reviewing, and analyzing data from several literature sources such as books, journals, and research relevant to this research. Data analysis uses the Miles and Huberman model. The results show that the implementation of multicultural Islamic education is a solution in building and strengthening the inclusive character of students in college through the integration of Islamic values with the curriculum, learning methods, and academic culture of higher education. Thus, multicultural Islamic education does not only focus on theoretical understanding, but also on efforts to internalize Islamic values in the learning process, thereby creating a tolerant and inclusive generation.